Warkite, Ca2Sc6Al6O20, a new mineral in carbonaceous chondrites and a key-stone phase in ultrarefractory inclusions from the solar nebula. (15th May 2020) - Ma, Chi; Krot, Alexander N.; Beckett, John R.; Nagashima, Kazuhide; Tschauner, Oliver; Rossman, George R.; Simon, Steven B.; Bischoff, Addi
Abstract: Warkite (IMA 2013-129) is a new Sc-rich ultrarefractory mineral in the rhönite group of the sapphirine supergroup. It has a P 1 ¯ aenigmatite-type structure with a = 10.367 Å, b = 10.756 Å, c = 8.895 Å, α = 106°, β = 96°, γ = 125°, and Z = 2, and general formula of Ca2 (Sc, Ti, Al, Mg, Zr)6 Al6 O20 . Warkite occurs as micrometer-sized crystals in eleven ultrarefractory Ca, Al-rich inclusions (UR CAIs) from the CM, CV, CO, and CH chondrites. In the CM, CO, and CV CAIs, warkite in the cores coexists with a Ti-rich oxide, either perovskite or kangite; the cores are generally mantled and rimmed by davisite and/or Sc-diopside. In the CH CAIs and one CO CAI, warkite in the cores coexists with perovskite and grossite; the cores are mantled by grossite ± gehlenite, and rimmed by low-Sc, Al-diopside. Therefore, there are two basic families of warkite-bearing inclusions, those containing Sc-rich clinopyroxene but no grossite and those containing grossite but no Sc-rich clinopyroxene. Scandian clinopyroxene in warkite-bearing CAIs generally formed by the reaction of warkite, which supplied most or all of the Sc, Ti, and Al, and a nebular gas that supplied much of the Ca and O and virtually all of the Mg and Si. The presence of Sc-rich clinopyroxenes may reflect exposure of some warkite-bearing CAIs to a dust-rich environment, which would enhance partial pressures of Si-, Mg-, and Ca-bearing species in the vapor and make it oxidizing relative to a dust-poor gas. Warkite in grossite-bearing inclusions is generally Ti 3+ -enriched relative to those in davisite-bearing inclusions, consistent with their formation in relatively dust-poor, more-reducing environments. Warkite compositions are sensitive to the presence or absence of spinel, melilite, Sc-rich clinopyroxenes, and grossite. Compositional variations of perovskite and warkite grains indicate a connection but, except for late-stage Fe exchange, they did not equilibrate with each other. The presence of at least two trends in Y-Sc among perovskites without corresponding trends in warkite suggests that at least some perovskite formed separately. Warkite-bearing CAIs from CM2s and CO3.0s are uniformly 16 O-rich (Δ 17 O ∼ −23‰), whereas those from metamorphosed COs and CVs are isotopically heterogeneous: warkite, kangite, perovskite, melilite, and davisite are 16 O-depleted to various degrees (Δ 17 O range from −22 to −2‰) relative to hibonite, spinel, and forsterite, all having 16 O-rich compositions (Δ 17 O ∼ − 25 to −20‰). We infer that warkite-bearing CAIs originated in an 16 O-rich nebular gas. Subsequently, CAIs from metamorphosed CVs and COs experienced O-isotope exchange with an 16 O-depleted external reservoir, most likely aqueous fluids on the CV and CO chondrite parent asteroids; however, O-isotope exchange in the solar nebula cannot be excluded.